Educational and developmental goals are important component for mathematics teaching process - Kozhabaev, K.G.; Gabdullin, R.S. (Вестник Карагандинского университета, 2016)
This article presents the goal-setting problem of teaching. Modern research shows that in the real learning process the goal has the fundamental place, so called «core» around which the teacher combines all the pedagogical means into the system locating each of them. Humanization of Education promoted the educational and developmental goals to the foreground, but few knows the differences in goals of education and development. The authors propose a model of educational and developmental learning, where the teacher comes to goal-setting process with the responsibility. The attention of teacher in the learning process is aimed at identifying the individual capabilities and interests of each student.
Keywords: Educational and developmental goals; learning process; education; development; personality; in- terest; educational and developing model; educational activity